The invisible city: The mundane biogeographies of urban microbial ecologies - Aaron Bradshaw (Geo: Geography and Environment)
Abstract More‐than‐human, multispecies and animal geographic accounts of the city have tended to focus on large, charismatic and wild organisms, to the detriment of spatially invisible other‐than‐humans that are central to urban reproduction. At the same time, urban microbial geographies have foregrounded embodied interactions between humans and microorganisms, whether they are symbiotic or pathogenic, often marginalising the material contributions of extracorporeal microbiomes to the urban fabric. Building from these two blindspots, this article focuses on microbial ecologies that live constitutively outside of (other‐than‐)human bodies and which are intimately caught up in the metabolic intensities and infrastructural environments of the urban realm. There are two key aims: (1) to explore different forms of urban microbial ecologies and (2) to examine their relationships with urban infrastructures and reproduction. My disciplinary lenses are animal geography, microbe studies and urban ecology and my case studies are focused on urban water metabolism. Thus, based on empirical fieldwork on the urban River Lea in East London and supplemented by scientific literature and technical documents, I analyse three urban microbial ecologies that correspond to the urban realms’ ‘extended microbiomes’: those involved in slow sand filtration for the treatment of drinkable water, those involved in sewage treatment via the activated sludge process and those emerging and evolving in disused urban canal infrastructure. These processes spatially manage microbial growth and modulate the distribution of different forms of microbial agency with important effects for the smooth functioning of urban water metabolism. I suggest these ecologies correspond to the ‘spaces' of microbes in the city, and characterise a mundane system of repetition and regulation. However, microbes continue to assert their agency within the spaces of urban water metabolism, create their own places and worlds and highlight a more‐than‐human contingency and indeterminacy at the heart of urban reproduction.